Uncovering Islamic Financial Literacy: A Case Study of Islamic Economics and Banking Students - Achmad Agus Priyono (Yayasan Letiges Konsultan Sosial, 2026)
Financial literacy is crucial for students to manage their finances intelligently and responsibly. Mastery of financial literacy serves not only as basic knowledge but also as a life skill that every individual must possess to support long-term survival. This knowledge helps students develop personal financial plans and improve their quality of life. Students in the Sharia Economics and Sharia Banking Study Programs receive courses related to financial institutions in the sixth to eighth semesters, so theoretically, they should possess financial literacy skills. Based on this situation, the researcher was interested in examining the level of financial literacy of students at the KH. Abdul Chalim Islamic Boarding School Institute focuses on Sharia Economics and Sharia Banking students. This study aims to measure Sharia financial literacy among students in that environment. The research method used was quantitative with a descriptive approach. The study population was 120 students, with a sample of 92 students determined using cluster sampling techniques. All data were analysed using descriptive statistics. The results showed that the level of Sharia financial literacy among students reached 71.46%. According to Chen and Volpe's classification, this achievement is considered moderate, while according to the Financial Services Authority (OJK) classification, it falls into the sufficient literacy category. The average score for basic sharia financial knowledge was 73.2%, sharia savings and loans 74.9%, sharia insurance 68.62%, and sharia investment 68.9%.